Compact rectenna array on-package for wirelessly powered small device - Zhang, Jun Wu (2015)
Wirelessly powered small device, as the name implies, is a device that powered by receiving radiated RF power. Rectenna, i.e, rectifying-antenna, is an integration of receiving antenna and rectifier circuit. The receiving antenna captures the incoming RF power and rectifier circuit converts the RF power received into DC power to power up the device. As technology advances, wirelessly powered small devices have evolved from simple UHF RFID tags to multi-functional devices like wireless sensor platform that integrates multiple functions such as sensing, computing and communication. Such devices are gaining research interests because of their potential to be deployed for long-term sensing in wide ranging of applications, such as embedded sensor for infrastructure health monitoring and medical application. These devices are usually designed to be light and small for ease of deployment. Each device usually integrated with a single receiving antenna and the antenna usually occupies significant space. It can be miniaturized but at the expense of efficiency and bandwidth. Also the power received by a single antenna is limited, which limits the functions that can be performed as well as the communication range of the device from the transmitter/reader. Thus the motivation of the work is to explore and develop a feasible solution of rectenna array implementation to enhance its power receiving capability and yet maintain compactness at the same time. This thesis documents the works accomplished to develop a compact rectenna array, which covers the elaboration of the motivation, design and simulation, implementation and measurement of the prototype. The RF receiving capabilities of the arrays have also been evaluated with the antenna array integrated with rectifier circuits. The results also show that the proposed design was capable of enhancing the RF receiving capability of the device with proper design of the array with decoupling element. The proposed design can be easily tuned to work at different UHF bands and migrated to any other fabrication technology, such as 3D printing technology.